PENGEMBANGAN E-BOOK INTERAKTIF TARI TOPENG SIDHAKARYA UNTUK MENINGKATKAN PEMAHAMAN TARI RITUAL SISWA SMP PASRAMAN : SEKOLAH SMP PASRAMAN SARASWATI 1 SURABAYA - Sekar Tunjung Ariawan Winarto; I Nengah Mariasa (Universitas Negeri Surabaya, 2025)
Topeng Sidhakarya is a UNESCO-recognized sacred Balinese mask dance taught at Pasraman Saraswati 1 Surabaya, a Hindu religious school with only three hours of weekly instruction. Conventional, one-way teaching leaves the 49 junior high level students with surface-level understanding of the dance's philosophy and symbolism. This research and development (R&D) study, using a mixed-methods approach and the ADDIE model, produced an interactive e-book accompanied by short knowledge videos covering the dance's history, meaning, function, dancer criteria, and purification ritual. The product was validated by a material expert, a media expert, and a language expert, then trialed with 10 students using a pretest-posttest design. Validation results showed the media was categorized as very feasible (material 93.00%, media 81.61%, language 96.36%, student response 90.00%). The N-Gain score reached 0.88, indicating a high level of effectiveness in improving students' understanding of the ritual dance. These findings suggest that interactive, multimedia-based e-books can meaningfully support cultural-religious arts education under limited contact-time conditions. Keywords: Interactive e-book, ritual dance, Topeng Sidhakarya, ADDIE model, learning media